2018
DOI: 10.1002/pip.3003
|View full text |Cite
|
Sign up to set email alerts
|

A comparative life cycle assessment of end‐of‐life treatment pathways for photovoltaic backsheets

Abstract: In light of growing photovoltaic (PV) installation capacities around the world, and with it the increasing number of decommissioned modules, it is vital that PV waste is duly treated to recover valuable materials as well as to comply with legislative requirements. The European Union (EU) directive on Waste Electrical and Electronic Equipment and the Restriction of Hazardous Substances mandates manufacturers, retailers, and importers to collectively organise and finance the end‐of‐life (EoL) stage of electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Obviously, the pyrolysis scenario is only theoretical and could be used only if recyclers were certain that no halogenated components were embodied in the PV panel. Aryan et al (2018) proved that the pyrolysis of fluorinated backsheets is unfeasible both from an economic as well as technical viewpoint. For this purpose, the study by Fraunhofer (2017) suggested the potential labelling (or marking) of PV panels by manufacturers, according to the fluorine content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Obviously, the pyrolysis scenario is only theoretical and could be used only if recyclers were certain that no halogenated components were embodied in the PV panel. Aryan et al (2018) proved that the pyrolysis of fluorinated backsheets is unfeasible both from an economic as well as technical viewpoint. For this purpose, the study by Fraunhofer (2017) suggested the potential labelling (or marking) of PV panels by manufacturers, according to the fluorine content.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, studies by Latunussa et al, 2016, Wambach, 2017, Aryan et al (2018) and Corcelli et al (2018) agree on the environmental significance of incinerating the halogenated plastics in the backsheet. Unfortunately, as reported by Wambach (2017), if the ‘halogen content is too high, then incineration in a specialised hazardous waste plant must be carried out’, in order to minimise the emission of potentially toxic air pollutants such as hydrogen fluoride (HF).…”
Section: Literature Review On Eol Treatments Of Pv Panelsmentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, Wade et al presented a comprehensive decision tree (Figure ) depicting the different options for EoL management of decommissioned PV systems. A significant number of scientific studies and public reports, as well as research projects and collaborative platforms have attempted over the last years to shed light on these different EoL paths and processes, with a major focus on PV recycling technologies, high‐value material recovery, downstream EoL management models (collection‐transportation‐recycling) and life cycle analyses. So far, insights from the reported literature have been rather fragmented and somewhat one‐sided, largely focusing on PV recycling processes and relevant innovation efforts.…”
Section: Introductionmentioning
confidence: 99%